Glossina spp. gut bacterial flora and their putative role in fly-hosted trypanosome development - Geiger, Anne; Fardeau, Marie-Laure; Njiokou, Flobert; Ollivier, Bernard (Frontiers in Cellular and Infection Microbiology, 2013)
Human African trypanosomiasis is caused by trypanosomes transmitted to humans by the tsetse fly, in which they accomplish their development into their infective metacyclic form. The crucial step in parasite survival occurs when it invades the fly midgut. Insect digestive enzymes and immune defenses may be involved in the modulation of the fly’s vector competence, together with bacteria that could be present in the fly’s midgut. In fact, in addition to the three bacterial symbionts that have previously been characterized, tsetse flies may harbor additional bacterial inhabitants. This review focuses on the diversity of the bacterial flora in Glossina, with regards to the fly species and their geographical distribution. The rationale was i) that these newly identified bacteria, associated with tsetse flies, may contribute to vector competence as was shown in other insects and ii) that differences may exist according to fly species and geographic area. A more complete knowledge of the bacterial microbiota of the tsetse fly and the role these bacteria play in tsetse biology may lead to novel ways of investigation in view of developing alternative anti-vector strategies for fighting human – and possibly animal – trypanosomiasis.